Impact of maternal emotional experiences at birth and self-regulation in preterm children: The role of early interactions. Issue 1 (February 2023) - Ionio, Chiara; Giannoni, Veronica; Colombo, Caterina; Ciuffo, Giulia; Landoni, Marta; Banfi, Anna; Balestriero, Marina; Scelsa, Barbara; Lista, Gianluca
Abstract: Background: Preterm birth can constitute an unexpected interruption of the transition to motherhood that can impact on a mother's well-being and her subsequent interactions with her child and, thus, be an important risk factor for the infant's emotional development. Aims: this study aims to shed light on early mother–child interactions, influenced by maternal symptomatology after childbirth, that can compromise a child's self-regulation ability. Method: A battery of self-report questionnaires was administered to 246 mothers a few days after their babies' birth. At 3 months of corrected infant age, mother–infant interactions were assessed using the GRS scales through video recording. At 12 and 24 months of corrected age, Bayley-III scales were administered to assess children's self-regulation ability. Results: Significant correlations were found among maternal symptomatology and GRS dimensions in ELBW children. Regressions results showed how GRS scores were predicted by various POMS subscales. Conclusions: Our results underline that maternal symptomatology could be a risk factor for the co-construction of interactive exchanges between mother and premature baby and for the long-term development of the infant's self-regulation ability.